Em uma PA, o 7º termo vale -49 é o 1º termo -73. Qual é a razão dessa PA?
Soluções para a tarefa
Respondido por
13
Use a fórmula do termo geral da PA:
![a_7=a_1+6r\\
\\
-49=-73+6r\\
\\
6r=-49+73\\
\\
6r=24\\
\\
\boxed{r=4} a_7=a_1+6r\\
\\
-49=-73+6r\\
\\
6r=-49+73\\
\\
6r=24\\
\\
\boxed{r=4}](https://tex.z-dn.net/?f=a_7%3Da_1%2B6r%5C%5C%0A%5C%5C%0A-49%3D-73%2B6r%5C%5C%0A%5C%5C%0A6r%3D-49%2B73%5C%5C%0A%5C%5C%0A6r%3D24%5C%5C%0A%5C%5C%0A%5Cboxed%7Br%3D4%7D)
Respondido por
4
Bom Dia!
________________________________________
Dados:
a1 → -73
n→ 7
r → ?
an → -49
________________________________________
An=a1+(n-1)·r
-49=-73+(7-1)·r
-49=-73+6r
-49+73=6r
6r=24
r=24/6
r=4
________________________________________
Att;Guilherme Lima
Perguntas interessantes
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Biologia,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás